Design and Preparation of Molybdenum–Dinitrogen Complexes with Ferrocenyldiphosphine and Pentamethylcyclopentadienyl Moieties as Auxiliary Ligands. Issue 36 (16th August 2013) - Miyazaki, Takamasa; Tanabe, Yoshiaki; Yuki, Masahiro; Miyake, Yoshihiro; Nakajima, Kazunari; Nishibayashi, Yoshiaki
<x xml:space="preserve">Abstract</x> Fix me! Molybdenum–dinitrogen complexes containing ferrocenyldiphosphine and pentamethylcyclopentadienyl moieties as auxiliary ligands have been designed, prepared, and characterized (see scheme). The ferrocenyldiphosphine works as a unique ligand to inhibit dissociation of dinitrogen, as well as to make the coordinated molecular dinitrogen reactive toward electrophiles.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>